Binding Energy and the Heat of Chemisorption on Metallic Catalysts — A Thermodynamic Aspect - Andrzej Stokłosa; Stefan S. Kurek; Barbara Laskowska (Adsorption Science & Technology)
The thermodynamic conditions necessary for the adsorption of gaseous molecules onto metals are discussed in this work. The differences and similarities between chemisorption and the formation of a solid oxidation product on metals are indicated. It was pointed out that the changes in the interactions between the surface metal atoms before and after adsorption must be followed by an energetic effect that would affect the value of the heat of chemisorption and its dependence on the surface coverage. The dependence of the heat of adsorption on the surface structures being formed and their concentration is discussed. It was shown that the relationships discussed in various published works between the values of the initial heat of adsorption and the formation enthalpies of the compounds are only experimental and not based on thermodynamic principles. The initial heats of adsorption, binding energies in gaseous molecules and cohesive energies for the oxidation products of metals are discussed for O 2 and H 2 chemisorption.